2016
DOI: 10.1097/mop.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Congenital melanocytic nevi: update in genetics and management

Abstract: The management of patients with CMN is complex. Neurologic involvement and melanoma remain the two most devastating complications. New, genetically targeted therapies for patients with complications may be of value, and research for potential therapies is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Cutaneous nevi have NRAS and BRAF mutations. 1 , 2 BRAF is a serine-threonine kinase and NRAS an isoform of the RAS family of GTPase proteins; and both activate the MAPK signaling cascade, which leads cell cycle progression and cell proliferation. Similarly, for all the conjunctival nevi in this study, immunoreactivity and mutational analysis allowed for identification of either an NRAS or BRAF aberration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cutaneous nevi have NRAS and BRAF mutations. 1 , 2 BRAF is a serine-threonine kinase and NRAS an isoform of the RAS family of GTPase proteins; and both activate the MAPK signaling cascade, which leads cell cycle progression and cell proliferation. Similarly, for all the conjunctival nevi in this study, immunoreactivity and mutational analysis allowed for identification of either an NRAS or BRAF aberration.…”
Section: Discussionmentioning
confidence: 99%
“…For cutaneous nevi, the presence of either a BRAF or NRAS mutation has been associated with specific clinical features. 1 4 For instance, congenital cutaneous nevi are more likely to harbor NRAS mutations, while acquired nevi have a propensity toward BRAF mutations. 1 3 One prior study on conjunctival nevi, that evaluated for BRAF mutations only, found no difference in the proportion of children and adults with mutant lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment should be individualized, taking into consideration the age of the patient, the size and location of the lesions, the risk of melanoma, the possibility of a NCM, and the presence of other congenital abnormalities or comorbidities. The prognosis depends on all of these factors [ 4 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%